2000
DOI: 10.1016/s1097-2765(00)80251-8
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of Proteins from the ER of S. cerevisiae Requires an Intact Unfolded Protein Response Pathway

Abstract: To dissect the requirements of membrane protein degradation from the ER, we expressed the mouse major histocompatibility complex class I heavy chain H-2K(b) in yeast. Like other proteins degraded from the ER, unassembled H-2K(b) heavy chains are not transported to the Golgi but are degraded in a proteasome-dependent manner. The overexpression of H-2K(b) heavy chains induces the unfolded protein response (UPR). In yeast mutants unable to mount the UPR, H-2K(b) heavy chains are greatly stabilized. This defect in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
135
2
1

Year Published

2000
2000
2008
2008

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 169 publications
(144 citation statements)
references
References 30 publications
6
135
2
1
Order By: Relevance
“…This agrees with the finding that treatment of human fibroblasts with SubAB during the early phase of CMV infection downregulates the expression of viral proteins even as late as 96 h after addition of the toxin (Buchkovich et al, 2008). Many reports have indicated that ERAD components are upregulated as part of UPR (Casagrande et al, 2000;Friedlander et al, 2000). However, we have not observed an upregulation of proteins involved in ERAD, such as proteasome subunits, p97/VCP or the channel forming protein derlin 1 even after 16 h of incubation with SubAB.…”
Section: Discusssionsupporting
confidence: 91%
See 3 more Smart Citations
“…This agrees with the finding that treatment of human fibroblasts with SubAB during the early phase of CMV infection downregulates the expression of viral proteins even as late as 96 h after addition of the toxin (Buchkovich et al, 2008). Many reports have indicated that ERAD components are upregulated as part of UPR (Casagrande et al, 2000;Friedlander et al, 2000). However, we have not observed an upregulation of proteins involved in ERAD, such as proteasome subunits, p97/VCP or the channel forming protein derlin 1 even after 16 h of incubation with SubAB.…”
Section: Discusssionsupporting
confidence: 91%
“…ERAD constitutively counteracts ER stress, eliminating misfolded proteins from the ER, however UPR induces its further activation through upregulation of its components (Casagrande et al, 2000;Friedlander et al, 2000). We therefore expected that treatment with SubAB would accelerate ERAD of αTCR.…”
Section: Discusssionmentioning
confidence: 99%
See 2 more Smart Citations
“…The transmembrane kinase and endoribonuclease Ire1p is a key member of the latter pathway, since deletion of its gene impairs protein degradation [53]. Ire1p spans the ER membrane with its N-terminal portion within the lumen, and with its catalytic kinase and endoribonuclease domains in the cytosol or nucleus.…”
Section: Ire1p and β-Propellersmentioning
confidence: 99%